Justicia secunda Vahl leaf fraction protects against acetaminophen-induced liver damage in rats by alleviating oxidative stress and enhancing membrane-bound phosphatase activities - Esther O Aimofumeh; Godswill N Anyasor; Ijeoma Esiaba (Asian Pacific Journal of Tropical Biomedicine, 2020)
Objective: To investigate the effect of Justicia secunda Vahl leaf fraction against acetaminophen-induced oxidative damage in the liver of rats. Methods: In vitro antioxidant assays were performed on Justicia secunda leaf fractions. Gas chromatography-mass spectrometry analytical method was done. Experimental animals were orally administered with 2 g/kg b.wt. acetaminophen, 100-500 mg/kg b.wt. Justicia secunda ethyl acetate leaf fraction (JSELF), and 100 mg/kg b.wt. silymarin. Blood and liver were collected to measure hepatic, oxidative stress, and membrane-bound phosphatase markers. Results: JSELF had significantly (P<0.05) high total antioxidant capacity and inhibition of lipid peroxidation. JSELF-treated animals had reduced plasma hepatic enzymes, serum C-reactive protein, and oxidized low-density lipoprotein while hepatic superoxide dismutase, catalase, and reduced glutathione levels were elevated compared with untreated control. Membrane-bound phosphatase activities were improved in JSELF-treated animals. GC-MS detected tentatively 7 antioxidants and 4 hepatoprotective compounds. Conclusions: JSELF could protect against oxidative stress and improve membrane-bound phosphatase activity in rats with acetaminophen-induced hepatic damage.